2023
DOI: 10.3390/diagnostics13193077
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Hidden Power of Uromodulin: A Promising Potential Biomarker for Kidney Diseases

Raïsa Thielemans,
Reinhart Speeckaert,
Charlotte Delrue
et al.

Abstract: Uromodulin, also known as Tamm-Horsfall protein, represents the predominant urinary protein in healthy individuals. Over the years, studies have revealed compelling associations between urinary and serum concentrations of uromodulin and various parameters, encompassing kidney function, graft survival, cardiovascular disease, glucose metabolism, and overall mortality. Consequently, there has been a growing interest in uromodulin as a novel and effective biomarker with potential applications in diverse clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 303 publications
(437 reference statements)
0
1
0
Order By: Relevance
“…Increased RBP4 has been suggested as a biomarker for renal damage and proteinuria (Ratajczyk et al, 2022), which has also been suggested for UMOD (Thielemans et al, 2023). Therefore, further studies need to address whether serum or urinary RBP4 or UMOD levels could be used as a potential biomarker for kidney disease onset and progression in BBS patients (Xun et al, 2018;Swa et al, 2022), similar to what has been suggested for UMOD in ADPKD (Cansever et al, 2021).…”
Section: Discussionmentioning
confidence: 82%
“…Increased RBP4 has been suggested as a biomarker for renal damage and proteinuria (Ratajczyk et al, 2022), which has also been suggested for UMOD (Thielemans et al, 2023). Therefore, further studies need to address whether serum or urinary RBP4 or UMOD levels could be used as a potential biomarker for kidney disease onset and progression in BBS patients (Xun et al, 2018;Swa et al, 2022), similar to what has been suggested for UMOD in ADPKD (Cansever et al, 2021).…”
Section: Discussionmentioning
confidence: 82%